British Naturalist Laura Roscoe Thornely (1860–1951), Taxonomist of Hydroids and Bryozoans - Dale R. Calder (Taxonomy, 2021)
Laura Roscoe Thornely was born on 6 March 1860 in Blundellsands, Lancashire, England. On approaching age 30, in the late 1880s, she became interested in the taxonomy of hydroids and bryozoans under Prof. W.A. Herdman at University College, Liverpool. Her studies during much of the 1890s were based largely on the relatively well-known fauna of the boreal northeastern North Atlantic Ocean. Around the turn of the century, however, her focus shifted to collections from the species-rich tropical Indo-West Pacific region, the hydroids and bryozoans of which were then little-known. The publications by Thornely on hydroids from the tropical western Pacific, from Sri Lanka, and from the Sudanese Red Sea, the most noteworthy of her works on the group, are still frequently cited. Concurrently, papers were published on the Bryozoa from Northern Ireland, the Indian Ocean, and Antarctica. Overall, she described 70 new species, with 26 of them based on hydroids and 44 on bryozoans; one hydroid species was assigned by her to a new genus. A person of affluent means, the motivation for her research appears to have been pure academic interest; she never held a university appointment or degree. Thornely died on 18 July 1951 at age 91 in Troutbeck, Westmorland, England.